2017
DOI: 10.3390/atmos8120234
|View full text |Cite
|
Sign up to set email alerts
|

Annual Variability of Black Carbon Concentrations Originating from Biomass and Fossil Fuel Combustion for the Suburban Aerosol in Athens, Greece

Abstract: Abstract:The objective of this work was to assess the yearly contribution of fossil fuel combustion (BC ff ) and wood burning (BC wb ) to equivalent black carbon (eBC) concentrations, in Athens, Greece. Measurements were conducted at a suburban site from March 2013 to February 2014 and included absorption coefficients at seven wavelengths and PM 2.5 chemical composition data for key biomass burning markers, i.e., levoglucosan, potassium (K) and elemental and organic carbon (EC, OC). A well-documented methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 57 publications
3
36
1
Order By: Relevance
“…Recently, Zotter et al (2017) recommended to use α ff = 0.9 and α wb = 1.68, obtained by fitting the model outputs (calculated with the absorption coefficients at 470 and 950 nm) against the fossil fraction of EC derived from 14 C measurements. At DEM site, a previous study showed that values of a wb below 1.7 were not appropriate for the specific site (Diapouli et al, 2017b). On top of that, during fire events, Ångström exponent values up to 2 have been observed at DEM.…”
Section: Source Apportionment Of Black Carbon From Fossil Fuel and Womentioning
confidence: 91%
“…Recently, Zotter et al (2017) recommended to use α ff = 0.9 and α wb = 1.68, obtained by fitting the model outputs (calculated with the absorption coefficients at 470 and 950 nm) against the fossil fraction of EC derived from 14 C measurements. At DEM site, a previous study showed that values of a wb below 1.7 were not appropriate for the specific site (Diapouli et al, 2017b). On top of that, during fire events, Ångström exponent values up to 2 have been observed at DEM.…”
Section: Source Apportionment Of Black Carbon From Fossil Fuel and Womentioning
confidence: 91%
“…Differences in the absorption coefficients calculated using f λ values calculated for an SSA of 0.8 (e.g. f 6 = 1.166) and those found in Drinovec et al, (2015) were found to be lower than 1 %. The performance of the loading compensation algorithm was examined using the approach described in Drinovec et al, (2015), where the dependence of the absorption Ångström exponent α to the attenuation of light is analysed.…”
Section: Aerosol Light Absorption and Equivalent Black Carbonmentioning
confidence: 72%
“…The aerosol light absorption coefficient, b abs , was retrieved at each station by means of a seven-wavelength (370,470,520,590,660,880 and 950 nm) Aethalometer (Magee Scientific Corp., Berkeley, CA 94703, USA) with a 5 min temporal resolution. At DEM, the new generation AE33 Aethalometer model was used, which provides a real-time compensation for multiple scattering in the filter matrix and loading effects using the DualSpot Technology ® (Drinovec et al, 2015). The AE33 sampled aerosol through a PM 2.5 cut-off inlet.…”
Section: Aerosol Light Absorption and Equivalent Black Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of these variabilities could bring information regarding the impact of the main carbon sources to particulate matter. In Diapouli et al [31], seasonal, weekly, and diurnal variability of equivalent black carbon (eBC) concentrations were investigated at a suburban site in Athens (Greece). A dataset was collected between 2013 and 2014 including absorption coefficients (at seven wavelengths), and PM 2.5 chemical composition data for key biomass burning markers (levoglucosan, K, EC, and OC).…”
Section: Trends Of Carbon Content In Atmospheric Aerosolsmentioning
confidence: 99%